Health and Strength. (London : Health and Strength Publ. Co., 1966)
Fonds Suzan Daniel (FSD)
F/02/016 Archief Roger Vertongen
Periodiciteit : tweewekelijks
Redactie : 5 Church Street, Camberwell, London SE 5
Engels
Periodiek